Numerical and experimental investigation of a droplet vitrification process: A thermofluidic analysis for cryopreservation - Alisson R.S. Silva; Jacqueline B. Copetti; André C. Monteiro; Marcelo Gotardo; Jeferson D. de Oliveira; Mario H. Macagnan; Elaine M. Cardoso; Karolyn Ogliari (Cryobiology, 2024)

Fungal growth, patulin accumulation and volatile profile in ‘Fuji Mishima’ apples under controlled atmosphere and dynamic controlled atmosphere - Ingrid D. dos Santos; Marlos E.Z. Fontana; Bruna Klein; Stephanie R. Ribeiro; Andrieli Stefanello; Fabio R. Thewes; Suele F. P. Schmidt; Marina V. Copetti; Auri Brackmann; Ionara R. Pizzutti; Roger Wagner (Food Additives & Contaminants: Part A, 2022)

Differences in bacterial composition between men’s and women’s restrooms and other common areas within a public building - Priscila Caroline Thiago Dobbler; Álvaro Macedo Laureano; Deise Schroder Sarzi; Ehidy Rocio Peña Cañón; Geferson Fernando Metz; Anderson Santos de Freitas; Beatriz Midori Takagaki; Cristiane Barbosa D´Oliveira; Victor Satler Pylro; André Carlos Copetti; Filipe Victoria; Marc Redmile-Gordon; et al. (Antonie van Leeuwenhoek, 2018)

Direct measurement of nutrient concentrations in freshwaters with a miniaturized analytical probe: evaluation and validation - D. Copetti; L. Valsecchi; A. G. Capodaglio; G. Tartari (Environmental Monitoring and Assessment, 2017)

Klotho Gene and Selective Serotonin Reuptake Inhibitors: Response to Treatment in Late-Life Major Depressive Disorder - Giulia Paroni; Davide Seripa; Andrea Fontana; Grazia D’Onofrio; Carolina Gravina; Maria Urbano; Filomena Addante; Madia Lozupone; Massimiliano Copetti; Alberto Pilotto; Antonio Greco; Francesco Panza (Molecular Neurobiology, 2017)

Endogenous origin of foams in lakes: a long-term analysis for Lake Maggiore (northern Italy) - F. Stefani; F. Salerno; D. Copetti; D. Rabuffetti; L. Guidetti; G. Torri; A. Naggi; M. Iacomini; G. Morabito; L. Guzzella (Hydrobiologia, 2016)

Inflow intrusions at multiple scales in a large temperate lake - S. Laborde; J. P. Antenucci; D. Copetti; J. Imberger (Limnology and Oceanography, 2010)
Lake Como receives inflows of vastly varying scales. The majority of the lake's water comes from the alpine inflows to the north, and much smaller inflows supply large amounts of pollutants in the south. We combined various data sets with a three‐dimensional hydrodynamic model to investigate the processes affecting the fate of these inflows with potential applications for management responses to both pollution and climate change effects. During the stratified period inflow waters from the northern alpine sources intrude in the metalimnion, undergo a deflection due to the Earth's rotation, and subsequently affect local flushing in a semi‐closed embayment receiving the shallower intrusions of the small polluted inflows.

Pulmonary aspergillosis outbreak in Rhea americana in Southern Brazil - Marina V. Copetti; Stefanie D. Segabinazi; Maristela L. Flores; Sydney H. Alves; Janio M. Santurio (Mycopathologia, 2004)